The impact of the war on Ukraine's foreign trade - Simakhova, А.О. (Економіка промисловості, 2024)
The article considers theoretical and practical aspects of the war's impact on Ukraine's foreign trade. The choice of the topic is due to the need to find new ways to minimize the negative impact of the war on the country's foreign trade. In the article, general scientific methods were used: methods of synthesis and analysis; data systematization and comparison; and SWOT-analysis. The information base of this article consisted of statistical data of the State Statistics Service of Ukraine, articles by scientists, and Internet sources. The article analyses the changes in the structure of foreign trade in goods in Ukraine in 2022 compared to 2021. An analysis of changes in the regional structure of Ukraine's foreign trade is carried out. It was found that the exports of Vinnytsia, Volyn, Zakarpattia, Lviv, Odesa, Rivne, Ternopil, Cherkasy, and Chernivtsi regions in 2022 were higher than in 2021. These regions concentrated significant export potential during the war. The main destructive factors of Ukraine's foreign trade development during the war were identified. These factors are: decrease in export and import volumes; negative foreign trade balance; logistical problems, restrictions on the movement of goods, destruction of infrastructure. It is predicted that as a result of the war, the commodity structure of production in Ukraine will change, preference will be given to defense industries. Recommendations for the Ukrainian government to minimize the negative effects of the war on Ukraine's foreign trade are proposed, including: tax benefits for Ukrainian entrepreneurs, support for small and medium-sized enterprises, diversification of product sales markets, development of the domestic market and stimulation of domestic consumption, promotion of high-tech exports, reconstruction and restoration of the infrastructure of Ukraine, etc. The scientific novelty of the article lies in the improvement of ways to minimize the negative impact of the war on Ukraine's foreign trade. The practical value of the article lies in the development of relevant recommendations. It is established that the development of foreign trade in Ukraine will contribute to the stabilization of the national economy and ensure economic growth in the post-war period. Розглянуто теоретичні та практичні аспекти впливу війни на зовнішню торгівлю України. Вибір теми зумовлений необхідністю пошуку нових шляхів мінімізації цього впливу. Використано загальнонаукові методи синтезу та аналізу, систематизації та порівняння даних. Інформаційну базу статті становлять статистичні дані Державної служби статистики України, публікації науковців, інтернет-джерела. Проаналізовано зміни в структурі зовнішньої торгівлі України у 2022 р. порівняно з 2021 р., а також у регіональній структурі зовнішньої торгівлі України. Виявлено, що обсяг експорту Вінницької, Волинської, Закарпатської, Львівської, Одеської, Рівненської, Тернопільської, Черкаської та Чернівецької областей у 2022 р. був більшим, ніж у 2021 р. Саме в цих регіонах під час війни був сконцентрований значний експортний потенціал. Визначено основні деструктивні чинники розвитку зовнішньої торгівлі України під час війни: зменшення обсягів експорту та імпорту; від'ємне сальдо зовнішньої торгівлі; логістичні проблеми, обмеження на переміщення товарів, руйнування інфраструктури. Спрогнозовано, що внаслідок війни зміниться товарна структура виробництва в Україні, перевага надаватиметься оборонним галузям. Запропоновано рекомендації для уряду щодо мінімізації негативного впливу війни на зовнішню торгівлю України, серед яких: податкові пільги для вітчизняних підприємців, підтримка малого та середнього бізнесу, диверсифікація ринків збуту продукції, розвиток внутрішнього ринку та стимулювання внутрішнього споживання, сприяння високотехнологічному експорту, реконструкція та відновлення інфраструктури України тощо. Встановлено, що розвиток зовнішньої торгівлі в Україні сприятиме стабілізації національної економіки та забезпеченню економічного зростання в післявоєнний період.